A qualidade da cortiça e a sua relação com a expressão génica no felogénio de Quercus suber - Ramos, Miguel de Jesus Nunes (2011)
The cork oak (Quercus suber) is an important species in Portugal, mainly due to the economic value of the cork it produces. Cork is produced by phellogen. In cork oaks, this meristematic tissue has few discontinuities and has a peak of activity in the spring. Every phellogen discontinuity will degenerate into cork defects, being pores and nail inclusions the most common and relevant to cork’s industry. Acknowledging that epigenetic processes are critical for plant development, their study in phellogen is essential. For this purpose, DNA methyltransferases were studied, by means of isolating sequences of each of its classes (MET, DRM and CMT) and one protein associated to MET1 (DMAP1). The analysis of its gene expression was performed in trees’ phellogens of both good and bad cork quality producers, after the evaluation of their quality by image analysis methods. Studies performed showed de novo methylation as the most significant in this tissue and a correlation was established between the QsMET2 and QsDMAP1 genes expressions and the defects’ coefficient measured, which revealed that these genes are important for the cork’s quality processes